Obtenção de fibras de PLA/PBAT por eletrofiação para aplicação em filtros de ar - Silva, Raul Pirolli da (2024)
Air quality is crucial for life on Earth, but it has been compromised by urbanization and industrialization, which increase the emission of pollutants such as gases, particulate matter, and microorganisms. Air filtration is an effective solution to reduce pollutant levels. The filtration process uses filters that separate pollutants from the air. Filters can be manufactured by various methods, with fibrous membranes being notable. These membranes can be produced through the electrospinning of polymer solutions. In this study, fibrous membranes were produced from the electrospinning of a polylactic acid (PLA) and poly (butylene adipate-co-terephthalate) (PBAT) polymer solution in a 1/1 (w/w) ratio, using a dichloromethane/formic acid (9/1, v/v) mixture as the solvent. The polymer solution concentration was varied between 10 and 20% (w/v), the working distance between 10 and 18 cm, the voltage between 10 and 20 kV, and the injection rate between 0.5 and 1.5 mL/h, through a 2^4 factorial design. FTIR, DSC, and TG characterized the polymers and electrospun blends. In contrast, the membranes formed from the blend fibers were analyzed via scanning electron microscopy and subjected to particulate material filtration tests. The chemical structure, thermal stability, and thermal transitions of the fibrous membranes were not significantly affected by concentration and process parameters under the conditions adopted in the factorial design. The fibers exhibited a non-oriented morphology. A high quantity of beads was observed for fibers obtained with a polymer concentration (w/v) of 10%. In comparison, the quantity of beads was low or nonexistent for fibers obtained with solution concentrations of 15% and 20%. The average fiber diameter ranged from 458 ± 147 nm to 1239 ± 467 nm. The reduction in diameter was directly proportional to the reduction in concentration, with the concentration of the solution contributing 59.8% to the diameter reduction. Filtration analysis showed values from 44.53% to 99.76% for filtration efficiency of particulate matter. The solution concentration was the major contributing parameter to filtration efficiency, contributing 75.37%, with lower concentrations yielding higher efficiency, data obtained from statistical analysis of factorial planning 2^4 . Finally, it can be concluded that the electrospun PLA/PBAT membranes obtained in this study show potential for filtering particulate matter down to 0.3 µm.